THE NECESSITY OF THE METHODOLOGY FOR DEVELOPING THE DIGITAL COMPETENCES OF FUTURE ELEMENTARY SCHOOL TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Teaching is a complex activity. Competent teachers apply broad, deep, and integrated sets of knowledge and skills as they plan for, implement, and revise instruction. The use of information communication technology must be carefully planned and put into a pedagogical framework. It requires the teacher to possess good pedagogical and didactical knowledge.